Epicardial Fibrosis Explains Increased Endo–Epicardial Dissociation and Epicardial Breakthroughs in Human Atrial Fibrillation - Gharaviri, Ali; Bidar, Elham; Potse, Mark; Zeemering, Stef; Verheule, Sander; Pezzuto, Simone; Krause, Rolf; Maessen, Jos G.; Auricchio, Angelo; Schotten, Ulrich (Frontiers in Physiology, 2020)
Background Atrial fibrillation (AF) is accompanied by progressive epicardial fibrosis, dissociation of electrical activity between the epicardial layer and the endocardial bundle network, and transmural conduction (breakthrough). However, causal relationships between these phenomena have not been demonstrated yet. Our goal was to test the hypothesis that epicardial fibrosis suffices to increase endo-epicardial dissociation (EED) and breakthroughs during AF. Methods We simulated the effect of fibrosis in the epicardial layer on EED and breakthrough in a detailed, high-resolution, 3-dimensional model of the human atria with realistic electrophysiology. The model results were compared with simultaneous endo-epicardial mapping in human atria. The model geometry, specifically built for this study, was based on MR images and histo-anatomical studies. Clinical data were obtained in 4 patients with longstanding persistent AF and 3 patients without a history of AF. Results The AF cycle length, conduction velocity, and EED were comparable in the mapping studies and the simulations. EED increased from 24.13.4% to 56.586.2, (p<0.05), and number of breakthroughs per cycle from 0.890.55 to 6.742.11, (p<0.05), in different degrees of fibrosis in the epicardial layer. In both mapping data and simulations, EED correlated with prevalence of breakthroughs. Fibrosis also increased the number of fibrillation waves per cycle in the model. Conclusion A realistic 3D computer model of AF in which epicardial fibrosis was increased, in the absence of other pathological changes, showed increases in EED and epicardial breakthrough comparable to those in longstanding persistent AF. Thus, epicardial fibrosis can explain both phenomena.